Sheep grazing as sustainable vegetation management for solar energy production in the northeastern USA - Andrew, Alyssa C.; Antoszewski, Kevin; Goldberg, Zachary A.; Barter, Jonathan; Hain, Lexie; DeSario, Allison; White, Alissa; Roszell, Caro; Cole, Emily; Peterson, Stacie; Meys, Bethany (Frontiers in Sustainable Food Systems, 2025)
The expansion of solar photovoltaic production necessitates the need for vegetation management at solar sites. Solar grazing, an agrivoltaic (APV) approach involving vegetation management with livestock, is a rapidly growing solution to fill this need. Despite approximately 7–11% of existing installed solar capacity utilizing solar grazing in 2024, solar grazing research is still limited. The purpose of this study was to collect baseline data on how sheep grazing within commercial solar energy sites influences soil health, forage nutritive quality, and pasture conditions compared to mechanical mowing, along with understanding economic considerations for graziers, in the northeastern USA. In situ data was collected at 28 grazed and 3 non-grazed commercial solar sites in the northeastern USA from 2022 to 2024. At each site, samples were collected in “open space” (OS) - areas that were not directly underneath panels - and “under solar panel” (UP)—areas that were directly under solar panels. Soil health was monitored by collecting top-soil (0–15 cm) and sub-soil (15–30 cm) samples at grazed and non-grazed sites. Pasture Condition Scoring (PCS) was used to measure the pasture condition of only the grazed sites following the United States Department of Agriculture (USDA) Natural Resources Conservation Services (NRCS) Pasture Condition Scoring Sheet. Forage quality was assessed via exclusion cage harvesting methods. Organic matter, predicted soil protein, and active carbon values were all significantly higher at grazed sites than non-grazed sites (p < 0.001). Despite several differences among individual indicators, the overall total PCS score did not change over the study period. Forages harvested from UP in 2023 had significant higher crude protein (CP) content and significant better digestibility than those values observed in OS areas. Economic analysis emphasized the importance of long-term contracts and site control for the economic feasibility of grazing by demonstrating that costs can be reduced and become comparable to conventional mowing costs over time. Overall, this study highlights the potential for solar grazing as a beneficial alternative to mechanical mowing for enhanced ecologically sustainable vegetation management at solar sites, promoting biodiversity, soil health, forage quality, and local production.